An approach to the oral health situation in Uruguay - Piovesan Suárez, Sylvia (2020)
Oral health status in Uruguay was known after the national population survey carried out between 2010 and 2011. The most detected prevalent pathologies were caries and paradenciopathies. In addition, malocclusions, dental loss and mucosal lesions were studied. The information was complemented with other epidemiological studies, in relation with to temporomandibular disorders, which showed that half of the Uruguayan population presents symptoms and / or signs related to said disorder. The National Integrated Health System, which has been operating since 2008, concentrates public and private effectors and has attempted to comply with a National Oral Health Program. It provides prevention, promotion and treatment of oral pathologies of lesser complexity, so many benefits remain outside the system. Training human resources is sufficient to meet the needs of the population, but dentistry in general, and specialized, are very expensive and are not accessible to all who need it.